Cutting edge: hierarchy of chemokine receptor and TCR signals regulating T cell migration and proliferation. - Bromley, S; Peterson, D; Gunn, MD; Dustin, M (2000)
Chemokines play an important role in establishing the distribution of lymphocyte subpopulations in primary and secondary lymphoid tissues and in the recruitment of leukocytes to sites of inflammation. However, the potential of chemokines to down-regulate immune responses has not been demonstrated. We now show that certain chemokine gradients have the potential to suppress T cell activation by preventing formation of the immunological synapse, the specialized cell-cell junction that forms before a T cell can be fully activated. Our data reveals an immunosuppressive potential of chemokines engaging the CXCR3 and CCR7 receptors, but not the CXCR4, CCR2, CCR4, or CCR5 receptors. These results suggest a novel mechanism for T cell ignorance of agonist MHC-peptide complexes based on dominant chemokine gradients.